2022
DOI: 10.3389/fvets.2022.813524
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Neutrophil-to-Lymphocyte Ratio in Cats With Hypertrophic Cardiomyopathy

Abstract: ObjectiveTo assess the prognostic value of neutrophil-to-lymphocyte ratio (NLR) for cardiac death in cats with hypertrophic cardiomyopathy.Study DesignProspective observation study.AnimalsNinety-six client-owned cats.MethodsComplete blood count samples were collected from 38 healthy and 58 cats with hypertrophic cardiomyopathy (HCM), and the NLR ratios were analyzed. All cats had echocardiographic measurements performed on the same day as blood collection. Spearman rank correlation was used to assess the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
2
10
0
1
Order By: Relevance
“…Furthermore, NLR serves as a valuable biomarker for evaluating diseases such as chronic enteropathy, inflammatory bowel disease (IBD), protein-losing enteropathy, and duodenal lymphangiectasia in dogs [27][28]. Additionally, NLR offers insights into the disease progression in cats and dogs with pancreatitis [24], and it can serve as a useful marker for assessing the prognosis of hypertrophic cardiomyopathies in cats [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, NLR serves as a valuable biomarker for evaluating diseases such as chronic enteropathy, inflammatory bowel disease (IBD), protein-losing enteropathy, and duodenal lymphangiectasia in dogs [27][28]. Additionally, NLR offers insights into the disease progression in cats and dogs with pancreatitis [24], and it can serve as a useful marker for assessing the prognosis of hypertrophic cardiomyopathies in cats [17].…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the utility of leukocyte ratios in differentiating SIRS from sepsis in cats found that neutrophil-lymphocyte ratio (NLR) was associated with mortality in both SIRS and cats diagnosed sepsis [15]. NLR is used as an easily accessible parameter to assess the patient's inflammatory status and stress [16][17]. NLR is obtained by dividing the total neutrophil count by the lymphocyte count in the complete blood count (CBC) [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Типовими морфологічними змінами серцевого м'язу за ГКМП є гіпертрофія і дезорієнтація скоротливих м'язових волокон з поступовим розвитком фіброзу. Масивна гіпертрофія лівого шлуночка (понад 15 мм) відбувається через потовщення вільної стінки і міжшлуночкової перегородки з одночасним зменшенням об'єму порожнини [11][12]. У рідкісних випадках спостерігається гіпертрофія правого шлуночка, частіше асиметричного характеру з частим розвитком обструкції вихідного тракту за відсутності відомих причин.…”
Section: вступunclassified
“…In ammatory cells and signaling pathways are the pathological routes of development and progression of canine CHF (Rubio et al 2020). Besides evaluating the biomarkers of the in ammation such as cytokines (interleukins) and acute phase proteins (APPs; C-reactive protein in cats (Fries et al 2022).…”
Section: Introductionmentioning
confidence: 99%